(untitled) (Latakia University Journal -Basic Sciences Series, 2016)
The changes in coefficient of distribution of lead and cupper has been studied in system with two phases, liquid water contaminated with lead and copper-solid (natural Phosphate of Syria) correlation of the following factors: Time of mixing phases, size of the developed steel ,change the values of PH ,concentration of elemental lead and concentration of element capper ,the concentration of calcium as a competitor to the occupation of sites available on the solid phase, the ratio Vpresents the water phase size on the mass of phase ,the Percentage removal of lead from aqueous samples prepared in the laboratory91,57-99,95% were the best conditions for a vast proportion removed can be summarized as follows: PH=[6,63-10,11], Time of mixing phases =60 minutes and V/m=1000. The Percentage removal of copper from aqueous samples prepared in the laboratory 95,27 - 99,96% were the best conditions for a vast proportion removed can be summarized as follows: PH= [7,89-11,01] , Time of mixing phases =60 minutes and V/m=1000. Ideal conditions have been applied that were obtained according to laboratory tests on water samples from industrial input to Banias refinery and water samples from industrial drainage to Syrian company for oil transport after Removal for lead was( 100%,99 %). Removal for copper was( 100%,98 %) . درست تغيرات معامل توزع الرصاص والنحاس في منظومة ذات طورين [سائل (مياه ملوثة بالرصاص والنحاس) - صلب(فوسفات خام سورية )] وذلك بتابعية العوامل التالية زمن خلط الطورين,الحجم الحبيبي للطورالصلب, تغير قيم الأس الهيدروجيني PH, تركيز العنصر الملوث, تركيز عنصر الكالسيوم كعنصر منافس للمواقع المتاحة على الطور الصلب, النسبة v/m كنسبة تمثل حجم الطور المائي على كتلة الطور الصلب.تراوحت نسبة إزالة الرصاص من عينات المحاليل المائية المحضرة مخبرياﹰ91,57-99,95 % وكانت أفضل الشروط للحصول على أعلى نسبة إزالة للرصاص كالتالي: درجة حموضة تتراوح بين6,63-10,11 وزمن خلط للطورين يصل إلى 60m وبنسبة V/m تبلغ .1000 وتراوحت نسبة إزالة النحاس من عينات المحاليل المائية المحضرة مخبرياﹰ -95,27 99,96% وكانت أفضل الشروط للحصول على أعلى نسبة إزالة للنحاس كالتالي: درجة حموضة تتراوح بين7,89-11,01 وزمن خلط للطورين يصل 60m وبنسبة V/mتبلغ.1000 جرى تطبيق الشروط المثالية التي تم الحصول عليها مخبرياﹰ على عينات مأخوذه من مياه الدخل لوحدة المعالجة في شركة مصفاة بانياس ومياه دريناج مأخوذه من الشركة السورية لنقل النفط فكانت نسبة الإزالة للرصاص ( (100%,99 % وكانت نسبة إزالة النحاس ( (100%,98 % .